Foreign Direct Investment into the United States - Dutta, A; Theis, J; Su, R (The International Journal of Finance, 2007)
This paper examines the flow of international investment into the United States between 1998 and 2004. The impetus behind the paper was to examine the possible impact the terrorist act of September II, 2001 (often alluded to as 9/11) may have had on foreign direct investment into the United States (defined as inward FDI). The data is reported both annually and quarterly. First, the annual data between 1998-2004 is reviewed. In looking at significant differences between the two periods, quarterly data is examined, as annual aggregation would lead to too few data points. Inward FDI is reported by the Bureau of Economic Analysis by region and then by individual country. The quarter of 9/11/2001 is omitted as being the event defining quarter. In the dataset collected, there are 13 quarters pre- and post- the event quarter. At first glance, the world seems to have definitely lowered its FDI into the United States. However, further examination reveals that except for France, no other country shows a significant reduction in its investments into the United States post- 9/11, compared to their average investments pre- 9/11.